Corelation between antibiotic resistans and biofilm formation power of Pseudomonas aeruginosa - Mobina Mahmoudi Jouibari; Seyed reza Hosseini Doust (Islamic Azad University, 2018)
P. aeruginosa has been mentioned as the major causative agents of nosocomial infections. Pseudomonas infections are often serious and show different resistance to treatment due to distribution of antimicrobial resistance. Meanwhile, some strains are also able to form biofilm during contamination, which help bacteria to be even more persisyant to yreatment. We examined the antibiotic resistance pattern of P. aeruginosa clinical isolates against Gentamicin, Clarithromycin, Cephalosporin, Ciprofloxacin, Imipenem, Azithromycin, and Ceftazidime and the correlation of antibiotic resistance with biofilm forming capability of isolates. Seventy two P. aeruginosa were isolated from clinical samples, by culturing on bacteriology standard methods. The isolates were confirmed by standard bacteriology tests. The antibiotic resistance pattern of isolates against antibiotics were achieved by standard method of Kirby-Bauer. Biofilm forming power of isolates were examined according to Microtiter Dish Biofilm Formation Assay standard method. The data were analysed statistically to show the correlation between biofilm forming and antibiotic resistance phenomen. The resistance against tested antibiotics were observed by most of clinical isolates. 54% of isolates showed resistance against Azithromycin and Clarithromycin, while, only 21% showed anti- Ciprofloxacin. 10% of isolates were able to form biofilm (OD= 1.2), the biofilm forming isolates showed resistance at least against one antibiotic. A high rate of resistance was seen against ciprofloxacin (29.2%), Azitromicin (75%), Sephepim (58.3%), ceftazidime (40.3%), Claritromicin (75%) Gentamicin (50%) and imipenem (45.8%). In total, 93.1% of the isolates were characterized as MDRPA. Biofilm formation was seen in 91% of the isolates. The high rate of MDRPA and its ability to produce biofilm is an alarm for public health. The statistical analysis showed that biofilm production in the MDRPA isolates was significantly higher than that in the non-MDRPA isolates (P < 0.001). The analyze testet chi‌‌_square test and student test P value and spierman test.